In Silico Model of Musa acuminata Stem as an Anticancer on Oral Squamous Cell Carcinoma against EGFR - Rachmayani, Nevrila Dewi; Carabelly, Amy Nindia; Firdaus, I Wayan Arya Krishnawan; Apriasari, Maharani Laillyza; Utami, Juliyatin Putri (UI Scholars Hub, 2026)
Background: Oral squamous cell carcinoma (OSCC) is characterized by overexpression of the epidermal growth factor receptor (EGFR). Citral, eucalyptol, and caffeic acid phenethyl ester (CAPE), which are derived from Musa acuminata, have shown anticancer activity. This study evaluated the potential of citral, eucalyptol, and CAPE from Musa acuminata as anticancer agents for OSCC by targeting EGFR using an in silico approach. Methods: Potential biological activity was predicted using Prediction of Activity Spectra for Substances (PASS) Online. Molecular docking was conducted with AutoDock Vina, and BIOVIA Discovery Studio was used to analyze binding affinity, interaction types, and bond distances between the compounds and active-site residues of EGFR. Results: CAPE showed the strongest binding affinity (-8.6 kcal/mol), whereas citral and eucalyptol each showed a binding affinity of -5.4 kcal/mol. CAPE formed a conventional hydrogen bond with CYS775 at 2.65 Å and hydrophobic interactions with PHE856, LEU777, and MET766, through π-alkyl and π-π T-shaped interactions. These interaction distances were within the effective range of <3.5 Å, indicating a stable ligand-protein complex. Conclusions: These in silico findings suggest that CAPE derived from Musa acuminata is a promising anticancer candidate for OSCC through its interaction with EGFR.